2009
DOI: 10.1021/jo9005987
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Protections for Nucleoside 5′-Monophosphates: Comparative Study on the Removal of O-Acetyl and O-Acetyloxymethyl Protected 3-Hydroxy-2,2-bis(ethoxycarbonyl)propyl Groups

Abstract: The applicability of 3-acetyloxy-2,2-bis(ethoxycarbonyl)propyl and 3-acetyloxymethoxy-2,2-bis(ethoxycarbonyl)propyl groups as biodegradable phosphate protecting groups for nucleoside 5'-monophosphates has been studied in a HEPES buffer at pH 7.5. Enzymatic deacetylation with porcine carboxyesterase triggers the removal of the resulting 3-hydroxy-2,2-bis(ethoxycarbonyl)propyl and 3-hydroxymethoxy-2,2-bis(ethoxycarbonyl)propyl groups by retro-aldol condensation and consecutive half acetal hydrolysis and retro-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 64 publications
(23 reference statements)
0
27
0
Order By: Relevance
“…B) Dependence on preincubation time of 1a (10 μM) with Pol β. No inhibitor, ●; Preincubation time 42 : 5, ; 20, ○; 40, ■; 60, .…”
Section: Figurementioning
confidence: 99%
“…B) Dependence on preincubation time of 1a (10 μM) with Pol β. No inhibitor, ●; Preincubation time 42 : 5, ; 20, ○; 40, ■; 60, .…”
Section: Figurementioning
confidence: 99%
“…Previous studies have shown that replacement of the 3-AcO group with a 3-[(acetyloxy)methoxy] group accelerated the first enzymatic deacetylation of bis-substituted thymidine 5'-monophosphate by a factor of 25, and the deacetylation of the resulting negatively charged diester even more [15]. As indicated above, 3'-O-[(pivaloyloxy)methyl] protection did not afford a viable prodrug strategy for 2-5A.…”
Section: Results Andmentioning
confidence: 92%
“…The present work is aimed at evaluating the feasibility of an enzymetriggered prodrug strategy for the trimeric 2-5A. Our previous studies [15] indicate that the removal of the second 3-(acetyloxy)-2,2-bis(ethoxycarbonyl)propyl group, i.e., conversion of phosphodiester to monoester, is exceedingly slow, but replacing the Ac group with an AcOCH 2 group markedly accelerates the reaction. The negatively charged phosphate group must be protected to enhance the internalization and the 3'-OH to prevent its attack on the neighboring protected phosphate linkage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12] The 4-acetylthio-2,2-dimethyl-3-oxobutyl group is also removed by esterases, but it is also thermolabile, and can thus be removed even if the enzymatic reaction is sluggish. [12] The 4-acetylthio-2,2-dimethyl-3-oxobutyl group is also removed by esterases, but it is also thermolabile, and can thus be removed even if the enzymatic reaction is sluggish.…”
Section: Introductionmentioning
confidence: 99%